The Impact of Higher Education Loan System among Students from Low-Income Background in Tanzania - Nyoni, Watende Pius (European Scientific Journal, ESJ, 2018)
In spite of the initiatives which have been taken by the government of Tanzania towards access to higher education for qualified students who came from low - income backgrounds, the studies and real situation reveal the reality of how this group of people has been denied to parity and fair for accessing higher education. Thus, Tanzania government has established Higher Education Students Loans Board with the Act No.9 of 2004 aiming at giving assistance to the students who got admission in universities, but came from low-income families with no financial strength to support their schooling. However, since its inception higher education loans board had failed to identify students from low-income background resulting in some students dropping out or postpone their studies as they look for other sources of funds. This article is qualitative in nature with the use of document analysis technique. The author uses relevant literature, officially published statistical data and various theoretical justifications for examining the impact of HE loan towards students from low-income background. The results of this study identified some challenges leading to a misallocation of fund to the needy students, application of Means Testing being one of them. Meanwhile, the author concludes with careful planning and effective use of means testing with a sustainable operational mechanism which will address the issue of parity and justice for the needy students in accessing higher education in Tanzania.